Lithium-philic framework material as well as preparation method and application thereof

By forming a foam structure of zinc nanosheet stacking on the porous conductive framework material, the problem of volume change of metal lithium anode and lithium dendrites in lithium metal batteries is solved, and more uniform lithium deposition and higher cycling performance are achieved.

CN119153693APending Publication Date: 2024-12-17BEIJING CHJ AUTOMOTIVE TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310722670.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Volume changes in metal lithium anode during circulation and lithium dendrites generate problems in cycle stability and safety of lithium metal batteries, and the unevenness of existing three-dimensional framework materials during lithium ion deposition limits their application.

Method used

The porous conductive framework material and zinc cladding layer are used to form a foam structure of zinc nanosheet stacking through electroplating, reducing the heterogeneous nuclear energy barrier of metal lithium, promoting its uniform deposition, and improving cycling performance.

Benefits of technology

It significantly improves the circulation performance of lithium metal batteries, inhibits the growth of lithium dendrites, and enhances the stability and safety of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153693A_ABST
    Figure CN119153693A_ABST
Patent Text Reader

Abstract

The invention provides a lithium-philic framework material as well as a preparation method and application thereof. The lithium-loving framework material comprises a porous conductive framework material and a zinc coating layer, wherein the zinc coating layer is coated on the partial or whole surface of the porous conductive framework material. The preparation method comprises the following steps: placing a porous conductive framework material in a solution containing zinc ions, electroplating, and forming a zinc coating layer on the surface of the porous conductive framework material to obtain the lithium-loving framework material. The lithium-loving framework material provided by the invention can reduce the heterogeneous nucleation energy barrier of the metal lithium, and has a good effect of inducing the metal lithium to uniformly deposit; the composite material can be used in a lithium metal battery using a metal lithium negative electrode, and the cycle performance of the lithium metal battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a lithium-philic skeleton material and a preparation method and application thereof. Background Art

[0002] The rapid development of electric vehicles and portable electronic products has put forward higher requirements on the energy density of secondary batteries. Limited by the low theoretical specific capacity of graphite, the energy density of lithium-ion batteries with graphite as negative electrode material is gradually approaching its theoretical limit. Therefore, it is urgent to find negative electrode materials with higher specific capacity to meet the requirements of high specific energy secondary batteries.

[0003] Lithium metal anode is considered to be one of the most promising anode materials due to its extremely high theoretical specific capacity (3860mA·h / g) and extremely low electrode potential (-3.040Vvs. standard hydrogen electrode). However, the volume of metal lithium anode changes during the cycle, which deteriorates the cycle stability of the battery; and lithium dendrites are easily generated during the cycle, which may pierce the diaphragm, causing short circuits and thermal runaway in the battery. These problems have severely limited the practical application of metal lithium anode.

[0004] To solve the above problems, researchers have proposed a strategy to introduce three-dimensional skeleton materials into the metal lithium negative electrode. The three-dimensional conductive skeleton has a high specific surface area, which can significantly reduce the local current density of the negative electrode, thereby delaying the formation of lithium dendrites. The porous structure of the three-dimensional skeleton can limit the growth of lithium inside the pores, alleviating the volume expansion of metal lithium during the charging and discharging process. However, due to the high heterogeneous nucleation barrier of metal lithium on the skeleton material, lithium ions will preferentially nucleate at the local "hot spots" on the skeleton surface in the initial stage, resulting in uneven metal lithium deposition behavior, making it difficult for the three-dimensional skeleton to play the expected role.

[0005] Lithiophilic skeletons refer to skeleton materials that are conducive to the uniform nucleation of metallic lithium after the introduction of lithiophilic sites or surface modification. The introduction of lithiophilic skeletons can significantly reduce the heterogeneous nucleation energy barrier of metallic lithium, which is crucial to inhibit the growth of lithium dendrites and optimize the deposition behavior of metallic lithium. At present, there are few studies on lithiophilic skeletons, and more types of lithiophilic skeleton materials remain to be developed. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a lithium-philic skeleton material and a preparation method and application thereof. The lithium-philic skeleton material can reduce the heterogeneous nucleation energy barrier of metallic lithium and has a good effect of inducing metallic lithium deposition; the lithium-philic skeleton material is applied to a lithium metal battery using a metallic lithium negative electrode, which can significantly improve the cycle performance of the lithium metal battery.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a lithium-philic skeleton material, comprising: a porous conductive skeleton material and a zinc coating layer, wherein the zinc coating layer is coated on a partial or entire surface of the porous conductive skeleton material.

[0009] When the zinc coating layer is coated on a partial surface of the porous conductive skeleton material, the coating area can be island-shaped (ie, the coating areas are isolated from each other) or continuous. In the present invention, the zinc coating layer is preferably coated on the entire surface of the porous conductive skeleton material.

[0010] In the lithium-philic skeleton material provided by the present invention, zinc can form a lithium-zinc alloy with lithium, and its lattice layer spacing is close to that of metallic lithium, which can reduce the heterogeneous nucleation energy barrier of metallic lithium and has a good inducing deposition effect on metallic lithium.

[0011] In some embodiments of the present invention, the porous conductive skeleton material is selected from one of carbon paper, carbon cloth, copper mesh, foam copper and foam nickel.

[0012] In some embodiments of the present invention, the zinc coating layer is a foam structure. The zinc coating layer of the foam structure has a larger specific surface area and more lithium-philic sites, which helps to further promote the uniform deposition of metallic lithium.

[0013] In some embodiments of the present invention, the specific surface area of ​​the zinc coating layer is 1-500m 2 / g; for example, it can be 1m 2 / g, 5m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 30m 2 / g, 40m 2 / g, 50m 2 / g, 60m 2 / g, 80m 2 / g、100m 2 / g, 120m 2 / g, 150m 2 / g, 180m 2 / g, 200m 2 / g, 220m 2 / g, 250m 2 / g, 280m 2 / g、300m 2 / g, 320m 2 / g, 350m 2 / g, 380m 2 / g, 400m 2 / g, 420m2 / g, 450m 2 / g, 480m 2 / g or 500m 2 / g, etc.

[0014] In some embodiments of the present invention, the zinc coating layer is formed by stacking zinc nanosheets. After the zinc nanosheets are stacked, a loose and porous foam structure can be formed.

[0015] In some embodiments of the present invention, the pore size of the zinc coating layer is 200-500 nm; for example, it can be 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm.

[0016] In some embodiments of the present invention, the content of the zinc coating layer in the lithium-philic skeleton material is 0.01-10wt%, for example, it can be 0.01wt%, 0.02wt%, 0.03wt%, 0.05wt%, 0.06wt%, 0.08wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.3wt%, 1.5wt%, 1.6wt%, 1.8wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, etc.; preferably 0.02-2wt%.

[0017] By controlling the content of the zinc coating layer in the lithiophilic skeleton material within the above range, it is more conducive to the uniform deposition of metallic lithium. If the content of the zinc coating layer is too little, its inducing deposition effect on metallic lithium is weak, which is not conducive to the uniform deposition of metallic lithium; if the content of the zinc coating layer is too much, it may cause the structure of the lithiophilic skeleton material to be denser, which is also not conducive to the uniform deposition of metallic lithium.

[0018] In some embodiments of the present invention, the thickness of the zinc coating layer is 1-1000nm, for example, it can be 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 60nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm, etc.; preferably 30-500nm.

[0019] In a second aspect, the present invention provides a method for preparing the lithium-philic skeleton material as described in the first aspect, the preparation method comprising the following steps:

[0020] The porous conductive skeleton material is placed in a solution containing zinc ions and electroplated to form a zinc coating layer on the surface of the porous conductive skeleton material to obtain the lithium-philic skeleton material.

[0021] It is easy for a person skilled in the art to understand that, since zinc ions need to be reduced to metallic zinc during electroplating and deposited on the porous conductive skeleton material, the porous conductive skeleton material is the cathode during electroplating. The present invention does not impose any particular restrictions on the anode material, and a person skilled in the art can select it conventionally according to needs.

[0022] The present invention deposits metallic zinc on a porous conductive skeleton material by electroplating, so that the formed zinc coating layer has a foam structure formed by stacking zinc nanosheets, and the formed zinc coating is relatively uniform, and its structure can also be controlled by adjusting electroplating parameters (such as voltage, current, power-on waveform, etc.).

[0023] In some embodiments of the present invention, before the electroplating, the porous conductive skeleton material is also cleaned and dried. The solvent used for cleaning can be water and / or ethanol; the drying method can be vacuum drying or forced air drying.

[0024] In some embodiments of the present invention, the solute in the solution containing zinc ions is selected from one or more of ZnCl2, ZnSO4 and (CH3COO)2Zn.

[0025] In some embodiments of the present invention, the solvent in the solution containing zinc ions is water and / or ethanol.

[0026] In some embodiments of the present invention, the concentration of zinc ions in the zinc ion-containing solution is 0.001-1.0 mol / L, for example, 0.001 mol / L, 0.002 mol / L, 0.003 mol / L, 0.005 mol / L, 0.006 mol / L, 0.008 mol / L, 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.05 mol / L, 0.06 mol / L 1 / L, 0.08mol / L, 0.1mol / L, 0.12mol / L, 0.15mol / L, 0.18mol / L, 0.2mol / L, 0.25mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L or 1mol / L, etc.; preferably 0.005-0.2mol / L.

[0027] In the present invention, if the concentration of zinc ions is too low, the morphology of the deposits on the skeleton surface is uneven, mainly presenting a granular shape, and the required deposition time is long; if the concentration of zinc ions is too high, although the deposition time can be reduced, the deposited morphology is prone to agglomeration.

[0028] In some embodiments of the present invention, the electroplating method is a constant voltage method, a constant voltage pulse method, a constant current method or a constant current pulse method, preferably a constant voltage pulse method.

[0029] In the present invention, if the power-on state is maintained for a long time during electroplating, a thick diffusion layer will be formed at the interface between the cathode and the solution, which will reduce the metal ion concentration on the cathode surface, produce concentration polarization, and limit the speed of electrodeposition, resulting in poor quality of the zinc coating layer, and pinholes and pitting will appear. Pulse electroplating includes an interruption time, and the consumed metal ions use this time to diffuse and replenish near the cathode. When the next power-on time comes, the metal ion concentration near the cathode is restored, so that the coating morphology is uniform, so it is preferred to use a pulse method for electroplating. Compared with the constant current pulse method, the constant voltage pulse method is simpler to operate and the electroplating effect is more uniform, so the constant voltage pulse method is more preferred.

[0030] In some embodiments of the present invention, the electroplating voltage is 0.5-1.5V, for example, it can be 0.5V, 0.55V, 0.6V, 0.65V, 0.7V, 0.75V, 0.8V, 0.82V, 0.85V, 0.88V, 0.9V, 092V, 0.95V, 0.98V, 1.0V, 1.02V, 1.05V, 1.08V, 1.1V, 1.15V, 1.2V, 1.25V, 1.3V, 1.35V, 1.4V, 1.45V or 1.5V, etc.; preferably, it can be 0.8-1.1V.

[0031] In the present invention, if the electroplating voltage is too small, the electroplating effect cannot be achieved, and it is difficult for zinc ions to be reduced and deposited, which may cause some impurities to be reduced and precipitated; if the voltage is too large, exceeding the reduction potential of zinc ions, a good electroplating effect cannot be achieved, and the electroplating morphology is sparse and uneven.

[0032] In some embodiments of the present invention, the electroplating time is 0.0005-0.5h, for example, it can be 4s, 10s, 20s, 30s, 50s, 80s, 100s, 120s, 130s, 150s, 160s, 170s, 180s, 190s, 200s, 210s, 220s, 230s, 240s, 250s, 260s, 280s, 300s, 320s, 350s, 380s, 400s, 420s, 450s, 480s, 500s, 550s, 10min, 15min, 20min, 25min, 30min, 40min, 50min or 1h, etc.; preferably 150-250s.

[0033] In some embodiments of the present invention, the power-on time in each cycle of the constant voltage pulse method is ≤60s, for example, it can be 60s, 55s, 50s, 45s, 40s, 35s, 30s, 25s, 20s, 15s, 10s, 5s, etc.; the interval time in each cycle accounts for a proportion of the cycle time that is ≥40%, for example, it can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc.

[0034] In a third aspect, the present invention provides an application of the lithium-philic skeleton material as described in the first aspect in a metallic lithium negative electrode.

[0035] In a fourth aspect, the present invention provides a composite metal lithium negative electrode material, comprising the lithium-philic skeleton material as described in the first aspect and a metal lithium layer.

[0036] In the present invention, there is no special limitation on the composite form of the lithiophilic skeleton material and the metallic lithium layer. For example, the lithiophilic skeleton material can be composited with a lithium belt or lithium sheet by rolling, or metallic lithium can be deposited on the lithiophilic skeleton material by physical, chemical or other means.

[0037] In some embodiments of the present invention, the thickness of the metallic lithium layer is 5-500 μm; for example, it can be 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm or 500 μm, etc.

[0038] In a fifth aspect, the present invention provides a lithium metal battery, comprising the composite metal lithium negative electrode material as described in the fourth aspect.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] In the lithium-philic skeleton material provided by the present invention, zinc can form a lithium-zinc alloy with lithium, and its lattice layer spacing is close to that of metallic lithium, which can reduce the heterogeneous nucleation energy barrier of metallic lithium and has a good effect of inducing metallic lithium deposition. The lithium-philic skeleton material is applied to a lithium metal battery using a metallic lithium negative electrode, which can inhibit the growth of lithium dendrites and significantly improve the cycle performance of the lithium metal battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The SEM image of the lithium-philic framework material provided in Example 2;

[0042] Figure 2 The SEM image of the lithium-philic framework material provided in Example 1;

[0043] Figure 3 The SEM image of the lithium-philic framework material provided in Example 3;

[0044] Figure 4 The lithium nucleation overpotential data diagram of the lithiophilic skeleton material and the copper mesh provided in Example 1;

[0045] Figure 5 This is a graph showing the cycling performance of a lithium-copper half-cell using the lithium-philic skeleton material and copper mesh provided in Example 1. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementations. It should be understood by those skilled in the art that the specific implementations are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0047] Example 1

[0048] This embodiment provides a lithium-philic skeleton material, including a porous conductive skeleton material, and a zinc coating layer coated on the porous conductive skeleton material, wherein the porous conductive skeleton material is a copper mesh.

[0049] The preparation method of the lithium-philic skeleton material in this embodiment is as follows:

[0050] (1) Cleaning a copper mesh (pore size of 50 μm, porosity of 80%, thickness of 50 μm) with ethanol and vacuum drying to obtain a clean copper mesh;

[0051] (2) preparing a solution containing zinc ions, wherein the solute is ZnCl2, the solvent is water, and the concentration is 0.01 mol / L;

[0052] (3) Placing the copper mesh in a solution containing zinc ions and electroplating it using a constant voltage pulse method, with an electroplating voltage of 1.0 V, a pulse cycle of 100 s, a power-on time of 50 s in one cycle, an interval time of 50 s, and a total electroplating time of 400 s;

[0053] (4) The electroplated copper mesh is taken out, cleaned with ethanol, and dried in a vacuum oven to obtain a lithium-philic skeleton material.

[0054] Example 2

[0055] This embodiment provides a lithium-philic skeleton material, which is different from Embodiment 1 only in that the total electroplating time is 100 s.

[0056] Example 3

[0057] This embodiment provides a lithium-philic skeleton material, which is different from Embodiment 1 only in that the total electroplating time is 800 s.

[0058] The surface morphology of the lithium-philic framework materials provided in Examples 1-3 was characterized by scanning electron microscopy (SEM). The SEM images of the lithium-philic framework materials with electroplating times of 100 s, 400 s, and 800 s were as follows: Figure 1 , Figure 2 , Figure 3 As shown in the figure, when the electroplating time is 100s, due to the short electroplating time, only a part of the zinc nanoparticles are deposited on the surface of the copper mesh, forming an island-like coating; when the electroplating time is 400s and 800s, a foam-like zinc coating layer composed of stacked zinc nanosheets is formed on the entire surface of the copper mesh; when the electroplating time is 400s, the morphology of the zinc nanosheets is more uniform.

[0059] Example 4

[0060] This embodiment provides a lithium-philic skeleton material, which is different from the embodiment 1 only in that the electroplating voltage is 0.7V.

[0061] Example 5

[0062] This embodiment provides a lithium-philic skeleton material, which is different from the embodiment 1 only in that the electroplating voltage is 1.2V.

[0063] Example 6

[0064] This embodiment provides a lithium-philic skeleton material, including a porous conductive skeleton material, and a zinc coating layer coated on the porous conductive skeleton material, wherein the porous conductive skeleton material is a carbon fiber cloth.

[0065] The preparation method of the lithium-philic skeleton material in this embodiment is as follows:

[0066] (1) Cleaning a carbon fiber cloth (carbon fiber pore size: 30 μm, porosity: 80%, thickness: 50 μm) with ethanol and vacuum drying to obtain a clean carbon fiber cloth;

[0067] (2) preparing a solution containing zinc ions, wherein the solute is ZnCl2, the solvent is water, and the concentration is 0.01 mol / L;

[0068] (3) placing the carbon fiber in a solution containing zinc ions and electroplating it using a constant voltage pulse method, with an electroplating voltage of 1.0 V, a pulse period of 100 s, a power-on time of 50 s in one cycle, an interval time of 50 s, and a total electroplating time of 400 s;

[0069] (4) The electroplated carbon fiber cloth is taken out, washed with ethanol, and dried in a vacuum oven to obtain a lithium-philic skeleton material.

[0070] Example 7

[0071] This embodiment provides a lithium-philic skeleton material, including a porous conductive skeleton material, and a zinc coating layer coated on the porous conductive skeleton material, wherein the porous conductive skeleton material is a carbon fiber cloth.

[0072] The preparation method of the lithium-philic skeleton material in this embodiment is as follows:

[0073] (1) Cleaning a carbon fiber cloth (carbon fiber pore size: 30 μm, porosity: 80%, thickness: 50 μm) with ethanol and vacuum drying to obtain a clean carbon fiber cloth;

[0074] (2) preparing a solution containing zinc ions, wherein the solute is ZnSO4, the solvent is water, and the concentration is 0.001 mol / L;

[0075] (3) placing the carbon fiber in a solution containing zinc ions and electroplating it using a constant voltage pulse method, with an electroplating voltage of 1.5 V, a pulse cycle of 100 s, a power-on time of 50 s in one cycle, an interval time of 50 s, and a total electroplating time of 500 s;

[0076] (4) The electroplated carbon fiber cloth is taken out, washed with ethanol, and dried in a vacuum oven to obtain a lithium-philic skeleton material.

[0077] Example 8

[0078] This embodiment provides a lithium-philic skeleton material, including a porous conductive skeleton material, and a zinc coating layer coated on the porous conductive skeleton material, wherein the porous conductive skeleton material is a carbon fiber cloth.

[0079] The preparation method of the lithium-philic skeleton material in this embodiment is as follows:

[0080] (1) Cleaning a carbon fiber cloth (carbon fiber pore size: 30 μm, porosity: 80%, thickness: 50 μm) with ethanol and vacuum drying to obtain a clean carbon fiber cloth;

[0081] (2) preparing a solution containing zinc ions, wherein the solute is (CH3COO)2Zn, the solvent is water, and the concentration is 1.0 mol / L;

[0082] (3) placing the carbon fiber in a solution containing zinc ions and electroplating it using a constant voltage pulse method, with an electroplating voltage of 0.7 V, a pulse cycle of 100 s, a power-on time of 50 s in one cycle, an interval time of 50 s, and a total electroplating time of 300 s;

[0083] (4) The electroplated carbon fiber cloth is taken out, washed with ethanol, and dried in a vacuum oven to obtain a lithium-philic skeleton material.

[0084] Example 9

[0085] This embodiment provides a lithium-philic skeleton material, including a porous conductive skeleton material, and a zinc coating layer coated on the porous conductive skeleton material, wherein the porous conductive skeleton material is foamed copper.

[0086] The preparation method of the lithium-philic skeleton material in this embodiment is as follows:

[0087] (1) cleaning the foam copper (pore diameter of the foam copper is 40 μm, porosity is 80%, and thickness is 100 μm) with ethanol and vacuum drying to obtain a clean foam copper;

[0088] (2) preparing a solution containing zinc ions, wherein the solute is ZnCl2, the solvent is water, and the concentration is 0.01 mol / L;

[0089] (3) placing the foamed copper in a solution containing zinc ions and electroplating it using a constant voltage pulse method, with an electroplating voltage of 1.0 V, a pulse cycle of 100 s, a power-on time of 50 s in one cycle, an interval time of 50 s, and a total electroplating time of 400 s;

[0090] (4) The electroplated copper foam is taken out, cleaned with ethanol, and dried in a vacuum oven to obtain a lithium-philic skeleton material.

[0091] Example 10

[0092] This embodiment provides a lithium-philic skeleton material, including a porous conductive skeleton material, and a zinc coating layer coated on the porous conductive skeleton material, wherein the porous conductive skeleton material is foamed copper.

[0093] The preparation method of the lithium-philic skeleton material in this embodiment is as follows:

[0094] (1) cleaning the foam copper (pore diameter of the foam copper is 40 μm, porosity is 80%, and thickness is 100 μm) with ethanol and vacuum drying to obtain a clean foam copper;

[0095] (2) preparing a solution containing zinc ions, wherein the solute is ZnSO4, the solvent is water, and the concentration is 0.01 mol / L;

[0096] (3) placing the foamed copper in a solution containing zinc ions and electroplating it using a constant voltage pulse method, with an electroplating voltage of 1.0 V, a pulse cycle of 100 s, a power-on time of 50 s in one cycle, an interval time of 50 s, and a total electroplating time of 400 s;

[0097] (4) The electroplated copper foam is taken out, cleaned with ethanol, and dried in a vacuum oven to obtain a lithium-philic skeleton material.

[0098] Assembly of half-cell: The positive electrode uses the lithium-philic skeleton material provided in the above embodiments, and copper mesh, carbon fiber cloth, and foam copper are used as comparisons. The negative electrode uses 100 μm thick metallic lithium, the diaphragm uses a polypropylene diaphragm, and the electrolyte uses a FEC / DMC solution containing 1.0 mol / L LiPF6 (the volume ratio of FEC to DMC is 1:4).

[0099] The above half-cell was subjected to a cycle performance test, and the test method was as follows:

[0100] At a current density of 1.0 mA cm -2 Under the condition of constant current discharge, 3 mAh cm -2 The lithium capacity is then -2 Under the condition of , constant current charging is performed until the cut-off voltage is 1.0 V. The cycle life of the lithium copper half-cell is tested, the lithium nucleation overpotential during the first deposition cycle is calculated, and the number of cycles when the coulomb efficiency drops to 80% is calculated.

[0101] The results of the above tests are shown in Table 1 below:

[0102] Table 1

[0103] Frame material Zinc content (wt%) Lithium nucleation overpotential (mV) Number of cycles Example 1 0.5 34 160 Example 2 0.1 90 97 Example 3 1.0 50 110 Example 4 0.03 95 89 Example 5 0.07 85 92 Example 6 0.2 40 150 Example 7 0.02 93 105 Example 8 1.2 77 130 Example 9 0.6 60 138 Example 10 0.7 52 149 Copper mesh 0 125 80 Carbon fiber cloth 0 110 70 Copper foam 0 210 60

[0104] Among them, the lithium nucleation overpotential data of the lithiophilic skeleton material and the copper mesh provided in Example 1 are as follows: Figure 4 The cycling performance of the lithium-copper half-cell using the lithium-philic skeleton material and copper mesh provided in Example 1 is shown in Figure 5 shown.

[0105] It can be seen from the above test results that the lithium-philic skeleton material provided by the present invention can significantly reduce the heterogeneous nucleation energy barrier of metallic lithium; applying the lithium-philic skeleton material to a lithium metal battery using a metallic lithium negative electrode can significantly improve the cycle performance of the lithium metal battery.

[0106] Among them, compared with Example 1, Example 2 has a lower zinc content and uneven electroplating due to the short electroplating time, the lithium nucleation overpotential of the lithiophilic skeleton material increases, and the cycle performance of the battery decreases; Example 3 has a longer electroplating time, which causes the electroplated zinc to easily agglomerate, the structure of the zinc coating layer is denser, the lithium nucleation overpotential of the lithiophilic skeleton material increases, and the cycle performance of the battery also decreases.

[0107] Compared with Example 1, Example 4 has a lower electroplating voltage, resulting in a lower electroplated zinc content and poor cycle performance; Example 5 has a higher electroplating voltage, which deviates from the reduction potential of zinc ions and fails to achieve a good electroplating effect. The electroplated morphology is sparse, resulting in an insignificant improvement in the cycle performance.

[0108] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A lithium-philic framework material, characterized in that The lithium-philic skeleton material comprises: a porous conductive skeleton material and a zinc coating layer, wherein the zinc coating layer is coated on a part or all of the surface of the porous conductive skeleton material.

2. The lithium-philic framework material according to claim 1, characterized in that The porous conductive skeleton material is selected from one of carbon paper, carbon cloth, copper mesh, foam copper and foam nickel.

3. The lithium-philic framework material according to claim 1 or 2, characterized in that The zinc coating layer is a foam structure; Preferably, the specific surface area of ​​the zinc coating is 1-500m 2 / g; Preferably, the zinc coating layer is formed by stacking zinc nanosheets; Preferably, the pore size of the zinc coating layer is 200-500 nm.

4. The lithium-philic framework material according to any one of claims 1 to 3, characterized in that The content of the zinc coating layer in the lithium-philic skeleton material is 0.01-10wt%, preferably 0.02-2wt%; Preferably, the zinc coating layer has a thickness of 1-1000 nm, preferably 30-500 nm.

5. A method for preparing the lithium-philic framework material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The porous conductive skeleton material is placed in a solution containing zinc ions and electroplated to form a zinc coating layer on the surface of the porous conductive skeleton material to obtain the lithium-philic skeleton material.

6. The preparation method according to claim 5, characterized in that: The solute in the zinc ion-containing solution is selected from one or more of ZnCl2, ZnSO4 and (CH3COO)2Zn; Preferably, the solvent in the solution containing zinc ions is water and / or ethanol; Preferably, the concentration of zinc ions in the zinc ion-containing solution is 0.001-1.0 mol / L, preferably 0.005-0.2 mol / L; Preferably, the electroplating method is a constant voltage method, a constant voltage pulse method, a constant current method or a constant current pulse method, more preferably a constant voltage pulse method; Preferably, the electroplating voltage is 0.5-1.5V, preferably 0.8-1.1V; Preferably, the total power-on time of the electroplating is 0.0005-0.5h, preferably 150-250s; Preferably, the power-on time in each cycle of the constant voltage pulse method is ≤60s, and the ratio of the interval time in each cycle to the cycle time is ≥40%.

7. Use of the lithium-philic skeleton material as described in any one of claims 1 to 4 in a metallic lithium negative electrode.

8. A composite metal lithium negative electrode material, characterized in that: The method comprises the lithium-philic skeleton material as described in any one of claims 1 to 4 and a metallic lithium layer.

9. The composite metal lithium negative electrode material according to claim 8, characterized in that: The thickness of the metal lithium layer is 5-500 μm.

10. A lithium metal battery, characterized in that: Comprising the composite metal lithium negative electrode material as described in claim 9.